Comprehensive motor skills assessment in children with autism spectrum disorder yields global deficits. (20th May 2022) - Odeh, Christina E.; Gladfelter, Allison L.; Stoesser, Carolyn; Roth, Sarah
Abstract : Purpose: Although children with autism spectrum disorder (ASD) often display motor deficits, the nature of these motor deficits remains unspecified. The purpose of this study was to establish a robust motor profile in children with ASD across a wider range of motor skills by using two professionally administered standardized motor assessments alongside a parent report measure to capture a comprehensive view of motor performance compared to a group of neurotypical peers. Methods: Complex motor skills, balance and global motor performance were compared in twenty-four children, between the ages of 5–12 years, split into two groups: ASD and typically developing. The Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2) and the Movement Assessment Battery for Children, Second Edition (MABC-2) were used to examine skill performance. Motor proficiency was also collected using the parent/caregiver form of the Vineland Adaptive Behavior Scales, 3 rd edition (Vineland-3). Results: Children with ASD presented with significant differences in complex motor skills, balance skills, and global motor performance when compared to their neurotypical peers across all three measures. Conclusion: This preliminary study indicated that the children with ASD had greater difficulty with global motor performance, including more difficulty performing complex motor tasks and balance tasks compared to their neurotypical peers. The parents of the children with ASD reported decreased proficiency of motor skills. Overall, the children with ASD demonstrated deficits performing tasks that targeted strength, speed, agility, coordination and both static and dynamic balance. While manifestations of motor skill deficits specific to the ASD population are variable, physical therapists should be included in the ongoing assessment and implementation of comprehensive therapeutic plans for children with ASD.